Epidemiologic and clinical characteristics of human bocavirus infection in children hospitalized for acute respiratory tract infection in Qingdao, China - Wang, Wenjing; Guan, Renzheng; Liu, Ziran; Zhang, Feng; Sun, Rui; Liu, Sitong; Shi, Xiaoyan; Su, Zhilei; Liang, Rongxiang; Hao, Kangyu; Wang, Zhaoguo; Liu, Xianming (Frontiers in Microbiology, 2022)
Persistent infection and prolonged viral shedding of human bocavirus 1 (HBoV 1) in children were reported and the role of HBoV 1 as a sole causative pathogen for acute respiratory tract infection has yet to be established. While the reported prevalence of HBoV infection varies due to different detection methods and sampling criteria, the viral and bacterial etiology of HBoV infection using multiplex real-time PCR has yet to be reported. Here we aimed to further explore the pathogenicity of HBoV in patients with ARI by screening the viral and bacterial infections in children with ARI in Qingdao and comparing the epidemiological, clinical characteristics and etiological results. HBoV was identified in 28.1% of the samples and further sequencing analysis confirmed as HBoV 1. The rate of HBoV monoinfection was 75% and the rate of co-infection with bacteria was 66.1%, suggesting the need for continued monitoring of HBoV in children with acute respiratory infections. Clinical characterization suggests that HBoV infection may affect organ functions such as liver, kidney, heart and blood acid-base balance. Additionally, it is essential to promote awareness about the importance of disinfection and sterilization of the hospital environment and standardized operations. The interactions between HBoV and other pathogens remain to be investigated in further details in the future.